Additional file 7 of Genetic mapping and QTL analysis for peanut smut resistance - De Blas, Francisco Javier; Arias, René S.; Ballén-Taborda, Carolina; Mamani, Eva; Odinno, Claudio; Rosso, Melina; Costero, Beatriz P.; Bressano, Marina; Soave, Juan H.; Soave, Sara J.; Buteler, Mario I.; Seijo, J. Guillermo; et al. (SpringerNature, 2021)
Fil: De Blas, Francisco Javier. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.